2019
DOI: 10.1109/tasc.2019.2948993
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Dynamic Loss on Critical Current and n-Value of HTS Coated Conductors

Abstract: Properties of superconductors, such as critical current and n-value, have a significant impact on their loss characteristics. This impact is essential for the design of superconducting devices and their loss reduction, and therefore need to be thoroughly understood. The dependence of AC loss in high temperature superconductors (HTS) on these properties has been well studied. However, it is still unknown how dynamic loss is affected. This paper is to address this unsolved problem and provide comprehensive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…However, analytical loss calculations are imperfect in that the formulae have been derived based on some fundamental assumptions, e.g., constant critical current, homogenous external field, thin film approximation for HTS CCs, etc. [55][56][57][58][59][60][61][62][63][64]. Besides, the analytical equations are normally limited to simple structures, e.g., single tapes or wires; thus, in superconducting machines, the analytical equations are not enough to accurately quantify the practical AC loss.…”
Section: Modelling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, analytical loss calculations are imperfect in that the formulae have been derived based on some fundamental assumptions, e.g., constant critical current, homogenous external field, thin film approximation for HTS CCs, etc. [55][56][57][58][59][60][61][62][63][64]. Besides, the analytical equations are normally limited to simple structures, e.g., single tapes or wires; thus, in superconducting machines, the analytical equations are not enough to accurately quantify the practical AC loss.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…The dynamic loss is calculated by measuring the voltage along with the transport current of the coated conductor sample. The measurement method has been extensively applied to much experimental exploration of dynamic loss and dynamic resistance of HTS CCs [16,63,64,[158][159][160][161]. Ogawa has studied the magnetization loss and dynamic loss of an HTS pancake coil with a double pick-up coil method and found that the dynamic resistance can mitigate the DC of the coil when it is operated in the permanent current mode [135].…”
Section: Electric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are several reports on numerical simulations and experimental measurements on total loss of REBCO CCs [43,[51][52][53][54][55][56] , REBCO stacks [54] and REBCO coils [54][55][56] at 77 K. Only one experimental study was conducted on total loss of YBCO-123 CCs under perpendicular magnetic fields [51,52] , where the critical current of the coated conductor was around 40 A. This early-stage coated conductor cannot represent the performance of currently available commercial REBCO CCs.…”
Section: Introduction 11 Motivationmentioning
confidence: 99%
“…This early-stage coated conductor cannot represent the performance of currently available commercial REBCO CCs. The total loss of commercial REBCO CCs were calculated via finite element (FM) simulations, which analyzed the influence of DC currents and AC magnetic fields, instead of the loss evolving process [43,53,54] . The frequency dependence of total loss in REBCO CCs, stack and coils was also studied via FE simulations [54] , which lacked systematic studies on the influence of DC currents and magnetic fields to total loss.…”
Section: Introduction 11 Motivationmentioning
confidence: 99%